Analisis Perbandingan Tingkat Efektivitas Penerapan Peraturan Pajak UMKM di Indonesia, Malaysia, dan Filipina - Hetti Herawati; Yuli Nawangsasi; Winna Pratiwi (Jurnal Ekonomi Manajemen Perbankan, 2022)
The development of the potential of MSMEs and tax revenue in Indonesia is deemed necessary by comparing Indonesia's tax regulations with that of several Asean countries in order to produce appropriate tax regulations, so that they can provide optimal contributions to the country. The purpose of this study was to compare the effectiveness of the application of MSME tax regulations in Indonesia, Malaysia, and the Philippines. The object of this research is the application of MSME tax regulations in Indonesia, Malaysia and the Philippines. The research method uses a comparative descriptive method and types of secondary data. The data analysis technique used is the One Way ANOVA test with content analysis method. The results show that there are differences in the effectiveness of the implementation of tax regulations in Indonesia, Malaysia and the Philippines, namely in terms of criteria, in terms of the amount and application of tax rates and other policies that regulate the scope of activities. SMEs in the three countries